P56 Electronic patient records (EPR) and the impact on attendance within a level 3 sexual health service. (18th May 2015) - Loftus, Belinda; Robinson, Cheryl; Brady, Sophie
Abstract : Background: Staff complained that the introduction of the EPR in December 2013 slowed down their consultations and thought that attendances had reduced significantly as a result of having to "cap" walk in clinics and reduce the number of appointment slots. In the early months post implementation there were increasing reports of clinics overrunning and patients not waiting to be seen. Verbal complaints from patients rose as they felt the impact on the service. Over time as the EPR became established these concerns and complaints lessened. Aim: To identify whether or not the EPR has significantly impacted on the footfall of patients attending a level three sexual health service. Methods: Comparison data was extracted from IT system and inserted in to data sheets from a service analysis in 2010. Results: Discussion: The observed difference both for New and FU patients in 2010 and 2014 is small despite staff feeling there has been a negative effect on patient attendance. There has been active encouragement to decrease the number of FU patients to improve DNA rates, which has reduced by 32% (2010–2014). Overall in the year 2014 there is little evidence that the IT system has significantly impacted on the footfall of patients attending a level 3 service, despite clinics being minimised and appointments decreased to manage attendance levels.